2017
DOI: 10.3390/ijms18051090
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Characterization of Dual-Sensitive Fluorescent Nanogels for Enhancing Drug Delivery and Tracking Intracellular Drug Delivery

Abstract: Here, dual-sensitive fluorescent branched alginate-polyethyleneimine copolymer (bAPSC) nanogels were synthesized from thiolated alginate and stearoyl-derivatized branched polyethyleneimine. The formation of bAPSC conjugates was confirmed through proton nuclear magnetic resonance and Fourier transform infrared spectroscopy, whereas dynamic light scattering was used to measure the particle size and ζ potential of the nanogels. The fluorescent properties of the nanogels were confirmed through fluorescent spectros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 50 publications
0
5
0
Order By: Relevance
“…At each interval time, 3 mL of the released medium was collected and the absorbance was measured at 481 nm. Moreover, to keep the volume in the dialysis system constant, an equal amount of fresh buffer solution was replenished continuously according to previous protocols. , The amount of DOX released was compared with that of a pre-established calibration curve. The measurement was performed three times, and the cumulative release was analyzed based on the following formula: …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…At each interval time, 3 mL of the released medium was collected and the absorbance was measured at 481 nm. Moreover, to keep the volume in the dialysis system constant, an equal amount of fresh buffer solution was replenished continuously according to previous protocols. , The amount of DOX released was compared with that of a pre-established calibration curve. The measurement was performed three times, and the cumulative release was analyzed based on the following formula: …”
Section: Methodsmentioning
confidence: 99%
“…Moreover, to keep the volume in the dialysis system constant, an equal amount of fresh buffer solution was replenished continuously according to previous protocols. 62,63 The amount of DOX released was compared with that of a pre-established calibration curve. The measurement was performed three times, and the cumulative release was analyzed based on the following formula: cumulative release (%) the concentration of drug release the concentration of drug load 100 = × (4)…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
“…All measurements were performed at 20 ± 0.1 • C. The light scattering autocorrelation functions were obtained for scattering angles between 20 • and 150 • with an angular step of 5 • . The diffusion coefficients were obtained directly from the autocorrelation functions by using CONTIN algorithm for multiexponential decay analysis [25] built into the ALV-Correlator software (version 3.0).…”
Section: Hydrodynamic Diameter and Zeta Potential Determinationmentioning
confidence: 99%
“…Authors [24] reported that spectroscopic characteristics of dye-doped silica nanoparticles indicate a much higher photostability and brightness in comparison to the nanoparticles with free uncoupled dyes. As an alternative to solid fluorescent NPs, alginate gel-based systems were proposed [25].…”
Section: Introductionmentioning
confidence: 99%
“…As a branched polymer, PEI has been shown as an efficient base for nanogels synthesis that can be used for drug delivery. Alginate copolymer with hydrophobically modified PEI was shown to readily encapsulate doxorubicin, and the release is dependent on the environment pH and redox nature [58]. The obtained nanogels are also fluorescent, which adds another function of tracking the drug delivery.…”
Section: Navigating the Abundancementioning
confidence: 99%